2023
DOI: 10.31557/apjcp.2023.24.2.353
|View full text |Cite
|
Sign up to set email alerts
|

The Metastatic Spread of Breast Cancer Accelerates during Sleep: How the Study Design can Affect the Results

Abstract: Metastasis is the most common event that determines survival in patients with breast cancer. The benefits of appropriate sleep in enhancing cancer patients' prognosis have been demonstrated. Likewise, emerging evidence has noted the positive impacts of regular circadian rhythm on cancer survival. Proper sleep and regular circadian rhythm can help to improve the cancer prognosis by enhancing the immune system. Besides, circadian rhythm disruption can assist cancer progression by promoting systemic inflammation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Hormone replacement therapy, depending on type, duration, and timing, may elevate risk. Conversely, reproductive history, modifiable through family planning, influences risk; early menstruation, late menopause, and nulliparity or late childbirth increase susceptibility (Houshyari and Taghizadeh-Hesary, 2023;Svyatova et al, 2019). Breastfeeding, partly modifiable, contributes positively to risk reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Hormone replacement therapy, depending on type, duration, and timing, may elevate risk. Conversely, reproductive history, modifiable through family planning, influences risk; early menstruation, late menopause, and nulliparity or late childbirth increase susceptibility (Houshyari and Taghizadeh-Hesary, 2023;Svyatova et al, 2019). Breastfeeding, partly modifiable, contributes positively to risk reduction.…”
Section: Discussionmentioning
confidence: 99%
“…TAMs are highly plastic cells involved in various actions, including suppressing the immune system, promoting tumor angiogenesis, and increasing resistance of tumor cells to chemotherapy [100]. Poor prognosis in many types of cancer is directly related to the number of TAMs in the TME [59,103]. Studies have shown that in certain types of cancer, including lung, skin, head and neck, bladder, and ovarian cancer, miRNAs secreted by cancer cells can increase the recruitment of macrophages to the TME [102,[104][105][106][107][108].…”
Section: Exosomal Mirnas and Tumor-associated Macrophagesmentioning
confidence: 99%